Hubungan Dukungan Sosial Dengan Resiliensi Pada Pasien Yang Menjalani Hemodialisis Di RSUD Arifin Achmad Provinsi Riau - Husna, Nailul; Bayhakki, Bayhakki; Erwin, Erwin (Universitas Pahlawan Tuanku Tambusai, 2024)
Chronic renal failure patients often experience psychological problems that affect hemodialysis therapy. The existence of social support can encourage patients to rise from the difficulties experienced. The purpose of this study is to understand the relationship between the social and medical relationships of patients who are undergoing hemodialisis at RSUD Arifin Achmad Provinsi Riau. This study employs a deskriptif korelasi with cross-sectional data. The study's sample consists of 101 respondents who were selected using the purposive sampling technique based on specific criteria. The two types of analysis that are used are univariate analysis and bivariate analysis using chi-square. The results of the univariate analysis of 101 respondents indicate that 67 people (66.3%) and 46 people (45.5%) have good social relationships. The results of the bivariate analysis, which are p value (0,000) < α (0,05), indicate that social relationships have strong bonds with regard to the patients' resiliensi.